PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KINERJA PEGAWAI DIKANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIDENRENG RAPPANG - Mutmainnah; Jabbar, Abdul; Latif, Adam (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The purpose of this study was to determine how much influence motivation has on employee performance at the Population and Civil Registration Office of Sidenreng Rappang Regency. The population in this study was 960 people. The sample collection technique was purposive sampling. This type of research is Descriptive Quantitative. Data collection techniques used in this study were observation, questionnaires, literature studies. Data analysis techniques used were validation tests, reliability, and hypothesis testing using IBM SPSS and Likert Scale. The results of this study are the results of the questionnaire obtained from the recapitulation of the Information Technology Use variable 81% are in the "agree" category, the recapitulation of employee performance variables of 79% are in the "agree" category. Factors that influence employee performance are the ability factor is 71% and the motivation factor is 77%. The influence of the use of information technology on employee performance at the Population and Civil Registration Office of Sidenreng Rappang Regency is categorized as "Influential/Significant", from the ANOVA test, the F count obtained is 28.384 with a significance level of 0.01, this shows that the influence of the independent variable as a whole has a significant effect, and the probability is far above 0.05 partially t count (5.328) ≥ t table (1.98552) meaning that the influence of the use of information technology on employee performance at the Population and Civil Registration Office of Sidenreng Rappang Regency is 81%.